A fiber composite material and a method for producing and using the same

CN122976138APending Publication Date: 2026-10-27DONGFENG MOTOR GRP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611253986.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-18
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0004]针对现有新能源汽车轮拱内衬材料难以同时兼顾A级不燃高防火等级、宽频隔声减振、抗振动疲劳长效稳定、耐泥水侵蚀与轻量化多项性能指标,且通过粘结剂贴合的传统多层复合结构极易出现层间剥离、失效损毁的问题,本发明提供了一种纤维复合材料及其制备方法和应用

Benefits of technology

本发明提供了一种纤维复合材料及其制备方法和应用,该材料采用玄武岩纤维分级改性与同步气流铺网工艺制备得到连续梯度一体化结构,包括依次设置的抗冲击防火层、梯度阻尼减振层以及多孔吸声轻量化层。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_19
    Figure SMS_19
Patent Text Reader

Abstract

The application belongs to the field of high-performance fiber composites, and specifically discloses a fiber composite material, a preparation method and application thereof. The fiber composite material adopts basalt fiber hierarchical modification and synchronous airflow laying process, and a continuous gradient integrated structure of an impact-resistant fireproof layer, a gradient damping vibration reduction layer and a porous sound-absorbing lightweight layer is constructed, and there is no adhesive interface between the layers. Through unilateral gradient negative pressure impregnation, the damping component is anchored in the middle layer fiber network in situ, and is cured and formed through partitioned variable temperature and pressure, and a micron-level hydrophobic flow guide channel is generated in situ at the fiber interlaced nodes through temperature control cooling. The fireproof grade of the fiber composite material can reach A-grade non-combustible, and the fiber composite material has the performances of broadband sound insulation, anti-vibration layering and self-hydrophobicity, and the peeling risk of traditional multi-layer lamination is simultaneously eliminated through the continuous gradient integrated structure.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of high-performance fiber composite materials, and specifically relates to a fiber composite material, its preparation method, and its application. Background Technology

[0002] Wheel arch liners are critical protective components on the inner side of the wheels of new energy vehicles, located adjacent to the power battery pack, braking system, and high-temperature areas of the chassis. With the increasing number of new energy vehicles on the road, battery thermal runaway and fire accidents are becoming more frequent. Therefore, wheel arch liner materials must meet Class A fire resistance and high-temperature flame retardant requirements. Simultaneously, because the wheel arch area is subjected to tire noise, road noise, gravel impact, mud and water immersion, and high and low temperature cycling over long periods, they must also possess low VOC (Volatile Organic Compounds), lightweight design, and long-term aging resistance.

[0003] Existing wheel arch liner materials often employ a multi-layered composite structure, with different functional layers bonded together using adhesives. This structure exhibits significant interlayer interfaces, making it highly susceptible to delamination, hollowing, and even cracking under long-term high-frequency vibrations and alternating hot and cold temperatures in vehicles. Furthermore, traditional processes struggle to precisely control the distribution of damping slurry, easily leading to clogging of the sound-absorbing layer pores and a decline in sound insulation performance. Additionally, most existing materials fail to meet Class A non-combustible standards and rely on additional hydrophobic coatings to cope with muddy and wet environments, resulting in issues such as easy coating wear and high costs. Summary of the Invention

[0004] To address the challenge of existing wheel arch lining materials for new energy vehicles simultaneously achieving multiple performance indicators such as Class A non-combustible high fire resistance, wide-band sound insulation and vibration reduction, long-term stability against vibration fatigue, resistance to mud and water erosion, and lightweight design, and the inherent problem of interlayer delamination and failure in traditional multi-layer composite structures bonded with adhesives, this invention provides a fiber composite material, its preparation method, and its application. This fiber composite material comprises, sequentially arranged, an impact-resistant fireproof layer, a gradient damping vibration reduction layer, and a porous sound-absorbing lightweight layer. Specifically: the impact-resistant fireproof layer comprises hydrophobically treated basalt fibers and flame-retardant components; the gradient damping vibration reduction layer comprises basalt fibers modified with a coupling agent containing polar anchoring points and flame-retardant components; and the porous sound-absorbing lightweight layer comprises inertized basalt fibers and flame-retardant components. This continuous three-layer structure solves the problem of existing wheel arch lining materials for new energy vehicles failing to simultaneously achieve Class A fire resistance, wide-band vibration reduction, fatigue resistance, mud and water resistance, and lightweight design, avoiding the failure risk caused by interlayer delamination in traditional adhesive-bonded multi-layer structures.

[0005] This invention provides the following technical solution: This invention provides a fiber composite material comprising, in sequence, an impact-resistant and fire-resistant layer, a gradient damping layer, and a porous sound-absorbing and lightweight layer, wherein: The materials for the impact-resistant fireproof layer include hydrophobically treated basalt fibers and flame-retardant components; The materials of the gradient damping vibration reduction layer include basalt fibers modified with coupling agents containing polar anchoring points and flame-retardant components; The porous sound-absorbing lightweight layer is made of inert basalt fibers and flame-retardant components.

[0006] In conjunction with the first aspect, in some embodiments, in fiber composite materials: The length of the hydrophobicated basalt fibers is 3-5 mm; and / or, The diameter of the hydrophobically treated basalt fibers is 6–12 μm; and / or, The length of basalt fibers modified with a coupling agent containing polar anchoring sites is 8–12 mm; and / or, The diameter of basalt fibers modified with a coupling agent containing polar anchoring sites is 6–12 μm; and / or, The length of the inertized basalt fibers is 15–20 mm; and / or, The diameter of the inertized basalt fibers is 6~12 μm.

[0007] In conjunction with the first aspect, in some embodiments, the basalt fibers treated with hydrophobicity in the impact-resistant fireproof layer are arranged in a transverse orientation; and / or, the basalt fibers modified with a coupling agent containing polar anchoring sites in the gradient damping vibration reduction layer are arranged in a three-dimensional random interwoven pattern; and / or, the basalt fibers treated with inertization in the porous sound-absorbing lightweight layer are arranged in a vertical three-dimensional pattern.

[0008] In conjunction with the first aspect, in some embodiments, the density of the impact-resistant fireproof layer is ρ1, the density of the gradient damping vibration reduction layer is ρ2, the density of the porous sound-absorbing lightweight layer is ρ3, and so on, decreasing sequentially, wherein: ρ1 > ρ2 > ρ3; and / or, ρ1 is 145~180 kg / m 3 ; and / or, ρ2 is 95~125 kg / m 3 ; and / or, ρ3 is 45~70 kg / m 3 .

[0009] In conjunction with the first aspect, in some embodiments, the raw materials in the impact-resistant fireproof layer, the gradient damping vibration reduction layer, and the porous sound-absorbing lightweight layer include, by weight, 88-93 parts of modified basalt fiber, 7-11 parts of halogen-free high-temperature resistant phenolic resin binder, 9-14 parts of halogen-free flame-retardant damping slurry, 1-1.8 parts of nano-silica, and 0.4-0.9 parts of micron-sized boron nitride.

[0010] Secondly, the present invention provides a method for preparing the above-mentioned fiber composite material, comprising the following steps: Basalt fibers were graded by length and subjected to differential surface modification with silane treatment agent. After drying, hydrophobic basalt fibers, basalt fibers modified with coupling agent containing polar anchoring sites, and inert basalt fibers were obtained. A multi-channel synchronous airflow web-forming device is used to simultaneously lay up and form hydrophobic basalt fibers, basalt fibers modified with a coupling agent containing polar anchoring sites, and basalt fibers treated with inertization in a single operation, thereby preparing a continuous gradient fiber preform. Specifically: the hydrophobic basalt fibers are compacted and web-laid using a first pressure airflow process to form the first region of the continuous gradient fiber preform; the basalt fibers modified with the coupling agent containing polar anchoring sites are laid up using a second pressure airflow process with a three-dimensional random interweaving web to form the second region of the continuous gradient fiber preform; and the inert basalt fibers are loosely web-laid using a third pressure airflow process to form the third region of the continuous gradient fiber preform. The airflow kinetic energy or compaction intensity of the first, second, and third pressure airflow processes decreases sequentially. Along the thickness direction of the continuous gradient fiber preform, the second region is located between the first and third regions. Prepare an impregnation slurry, spray the impregnation slurry onto the surface of the third region of the continuous gradient fiber preform, apply negative pressure to one side of the first region of the continuous gradient fiber preform, and obtain the impregnated continuous gradient fiber preform. The impregnated gradient fiber preform is hot-pressed using an independently temperature-controlled upper and lower mold, and then cooled in a furnace to obtain the fiber composite material.

[0011] In conjunction with the second aspect, in some embodiments, during one-time synchronous lay-up molding, the density of the hydrophobicated basalt fibers laid in the first region is 125~145 kg / m³. 3 ; and / or, the density of the basalt fibers modified with a polar anchoring coupling agent laid in the second region is 80~100 kg / m³. 3 ; and / or, the density of the inertized basalt fibers laid in the third region is 40~60 kg / m³. 3 .

[0012] In conjunction with the second aspect, in some embodiments, the viscosity of the impregnation slurry is 800~1200 mPa. The negative pressure applied to one side of the first region of the continuous gradient fiber preform is 0.06~0.09 MPa.

[0013] In conjunction with the second aspect, in some embodiments, the control parameters of the independently temperature-controlled upper and lower molds include: the mold temperature corresponding to the first region is controlled at 200~230℃, the mold temperature corresponding to the third region is controlled at 150~180℃, and the average molding pressure is 0.7~0.8 MPa.

[0014] Thirdly, the present invention provides a wheel arch liner comprising the aforementioned fiber composite material.

[0015] Fourthly, the present invention provides a new energy vehicle, including a wheel and a wheel arch liner disposed inside the wheel, the wheel arch liner being made of the aforementioned fiber composite material.

[0016] Compared with the prior art, the present invention has at least the following beneficial effects: This invention provides a fiber composite material, its preparation method, and its application. The material is prepared by graded modification of basalt fibers and synchronous airflow web laying process to obtain a continuous gradient integrated structure, which includes an impact-resistant fireproof layer, a gradient damping vibration reduction layer, and a porous sound-absorbing lightweight layer arranged in sequence.

[0017] The material uses basalt fiber as its matrix and employs a continuous gradient thermal impedance structure to effectively block the high temperatures of battery thermal runaway and flame propagation. It protects the damping components from melting, flowing, and releasing toxic fumes at high temperatures, possessing inherent Class A non-combustible properties, significantly improving the safety protection level of the adjacent battery pack. Simultaneously, the continuous gradient density creates a smooth transition between acoustic and thermal impedance, avoiding interlayer sound wave reflection and thermal stress concentration. This achieves full-frequency noise reduction by reflecting low-to-mid-frequency tire noise in the outer impact-resistant and fireproof layer, dissipating structural vibration noise in the gradient damping layer, and absorbing high-frequency noise in the porous sound-absorbing lightweight layer. This gradient density structure is an integrated structure with low overall density and light weight. Compared to traditional wheel arch liners, this fiber composite material achieves lightweighting while maintaining ultra-high fire resistance, high sound insulation, and impact resistance. In addition, the damping component is in-situ anchored to the gradient damping vibration reduction layer in the middle layer by unilateral gradient negative pressure impregnation, and micron-level hydrophobic guiding micropores are generated in-situ by slow cooling in the furnace. These micropores can quickly guide the infiltrated water, ensuring that the porous structure is not blocked and that the sound insulation and fireproof performance are stable and do not decrease under humid conditions.

[0018] Performance characterization results show that, tested according to national and automotive industry standards, the fiber composite material meets the GB 8624-2012 Class A non-combustible fire rating, with a fire resistance limit of 132 minutes at 800℃; the average weighted sound insulation is 47.5 dB; it shows no damage or deformation after 100 impacts from 50 km / h gravel, and no delamination or cracking after 20 high and low temperature cycles from -40℃ to 120℃; the water absorption rate can be as low as 0.9%, and the sound insulation performance retention rate in humid environments can reach up to 96%; the overall density is 70 kg / m³, and the VOC content meets the GB / T 27630-2011 automotive interior environmental protection standard. The fiber composite material provided by this invention solves the problem that existing new energy vehicle wheel arch lining materials are difficult to simultaneously achieve Class A fire resistance, wide-frequency vibration reduction, fatigue resistance, mud and water resistance, and lightweight, avoiding the failure risk caused by interlayer delamination in traditional adhesive-bonded multi-layer structures. Detailed Implementation

[0019] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions of this invention will be clearly and completely described below in conjunction with the embodiments of this invention. Obviously, the described embodiments are only some, not all, of the embodiments of this invention. Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this invention.

[0020] This invention provides a fiber composite material comprising, in sequence, an impact-resistant and fire-resistant layer, a gradient damping layer, and a porous sound-absorbing and lightweight layer, wherein: The materials for the impact-resistant fireproof layer include hydrophobically treated basalt fibers and flame-retardant components; The materials of the gradient damping vibration reduction layer include basalt fibers modified with coupling agents containing polar anchoring points and flame-retardant components; The porous sound-absorbing lightweight layer is made of inert basalt fibers and flame-retardant components.

[0021] In some embodiments, the fiber composite material contains: The length of the hydrophobicated basalt fibers is 3-5 mm; and / or, The diameter of the hydrophobically treated basalt fibers is 6–12 μm; and / or, The length of basalt fibers modified with a coupling agent containing polar anchoring sites is 8–12 mm; and / or, The diameter of basalt fibers modified with a coupling agent containing polar anchoring sites is 6–12 μm; and / or, The length of the inertized basalt fibers is 15–20 mm; and / or, The diameter of the inertized basalt fibers is 6~12 μm.

[0022] Preferably, the hydrophobic basalt fibers have a length of 4 mm and a diameter of 8 μm; the basalt fibers modified with a coupling agent containing polar anchoring sites have a length of 10 mm and a diameter of 8 μm; and the inert basalt fibers have a length of 18 mm and a diameter of 8 μm. This invention employs a design of basalt fibers with a uniform diameter of 8 μm and differentiated length grades. The consistent diameter of the single filaments ensures the uniformity of the fiber's intrinsic strength and toughness, simplifying raw material control while improving interlayer entanglement compatibility. The outer 4 mm short fibers form a dense transverse arrangement, building a strong impact-resistant and Class A fire-resistant surface barrier and synergistically achieving hydrophobic conduction. The middle 10 mm medium-length fibers construct a three-dimensional interwoven network, providing sufficient anchoring sites for the damping components to dissipate vibrational sound energy, while also facilitating a continuous transition between the inner and outer layers at the fiber scale. The inner 18 mm long fibers build a fluffy, three-dimensional porous structure, efficiently absorbing low- and mid-frequency noise and supporting a lightweight effect. Compared to solutions with completely uniform fiber length and diameter, this graded design can precisely match the three layers of differentiated functional positioning. It achieves controllable impregnation of damping slurry through a continuous gradient of porosity, avoiding clogging of sound-absorbing pores. At the same time, it relies on the natural interweaving and entanglement of fibers to eliminate adhesive interfaces and prevent the risk of delamination under long-term vibration and thermal cycling.

[0023] In some embodiments, the basalt fibers treated with hydrophobicity in the impact-resistant fireproof layer are arranged in a transverse orientation; and / or, the basalt fibers modified with a coupling agent containing polar anchoring points in the gradient damping vibration reduction layer are arranged in a three-dimensional random interweaving; and / or, the basalt fibers treated with inertization in the porous sound-absorbing lightweight layer are arranged in a vertical three-dimensional arrangement.

[0024] The three-layer fiber arrangement employs a differentiated spatial layout, essentially a directional structural adaptation tailored to the functional positioning of each layer. Simultaneously, the gradual transition of the arrangement ensures the overall structural continuity of the material: the outer layer, with its lateral orientation, constructs a continuous in-plane fiber barrier, enhancing in-plane impact resistance and thermal insulation capabilities, thus matching the surface protection properties; the middle layer, with its three-dimensional, randomly interwoven arrangement, forms a multi-dimensional fiber network, providing ample physical anchoring points for the damping components to dissipate vibrational energy, while also spatially entangled with the fibers of the upper and lower layers, eliminating clear interlayer interfaces and improving overall structural stability; the inner layer, with its vertical, three-dimensional arrangement, constructs a connected pore system extending along the thickness direction, enhancing sound energy dissipation efficiency, while maintaining pore structure stability at low density with a vertical fiber skeleton, balancing sound absorption performance and lightweight requirements. Compared to a uniform arrangement across all layers, this design avoids the inherent limitations of a single structural form, creating a continuous performance gradient through a gradient transition of the arrangement, achieving a synergistic balance of multiple functions including protection, vibration reduction, sound absorption, and lightweighting.

[0025] In some embodiments, the density of the impact-resistant fireproof layer is ρ1, the density of the gradient damping vibration reduction layer is ρ2, the density of the porous sound-absorbing lightweight layer is ρ3, and so on, decreasing sequentially, wherein: ρ1 > ρ2 > ρ3; and / or, ρ1 is 145~180 kg / m 3 ; and / or, ρ2 is 95~125 kg / m 3 ; and / or, ρ3 is 45~70 kg / m 3 .

[0026] Preferably, ρ1 is 160 kg / m 3 ρ2 is 110 kg / m 3 ρ3 is 55 kg / m 3 The density of the impact-resistant fireproof layer, the gradient damping vibration reduction layer, and the porous sound-absorbing lightweight layer decreases sequentially along the thickness direction. This design achieves a precise match between structure and function through a continuous structural gradient: the outer high-density dense fiber provides impact resistance and thermal barrier, the middle medium-density network anchors the damping components and transfers stress, and the inner low-density high-porosity structure efficiently absorbs sound and reduces weight. Simultaneously, the gradual density change creates a smooth acoustic impedance gradient, reducing interface reflections and allowing sound waves to attenuate layer by layer, achieving a broadband synergy of sound insulation in the outer layer, dissipation in the middle layer, and sound absorption in the inner layer. Furthermore, the continuous stiffness transition eliminates interlayer stress concentration, releasing stress under vibration and alternating heating and cooling, reducing the risk of delamination, and improving stability. The decreasing density corresponds to an increasing porosity, and combined with a unilateral negative pressure impregnation process, a gradient distribution of the damping slurry can be achieved, avoiding clogging of the sound-absorbing pores, ultimately achieving a synergistic balance of multiple performance aspects: protection, vibration reduction, sound absorption, and lightweighting.

[0027] In some embodiments, the raw materials in the impact-resistant fireproof layer, the gradient damping vibration reduction layer, and the porous sound-absorbing lightweight layer include, by weight: 88-93 parts of modified basalt fiber, 7-11 parts of halogen-free high-temperature resistant phenolic resin binder, 9-14 parts of halogen-free flame-retardant damping slurry, 1-1.8 parts of nano-silica, and 0.4-0.9 parts of micron boron nitride.

[0028] Preferably, the mixture comprises 90 parts modified basalt fiber, 9 parts halogen-free high-temperature resistant phenolic resin binder, 11 parts halogen-free flame-retardant damping slurry, 1.2 parts nano-silica, and 0.6 parts micron-sized boron nitride. The impact-resistant fireproof layer, the gradient damping vibration reduction layer, and the porous sound-absorbing lightweight layer share the same raw material system, which can avoid thermal expansion mismatch and reduce interlayer stress. The composition comprises: 90 parts basalt fiber as the main framework, providing intrinsic non-combustibility and mechanical strength while reserving sufficient pore space and space to load functional components; 9 parts phenolic resin binder, which forms a strong bond at fiber nodes, ensuring structural integrity and anti-delamination, without blocking acoustic channels or affecting Class A fire resistance; 11 parts halogen-free flame-retardant damping slurry, precisely enriched in the middle layer through unilateral negative pressure impregnation, forming a continuous damping layer to dissipate vibrational energy without penetrating into the inner layer and blocking sound-absorbing pores, thus balancing vibration reduction and sound absorption; and 1.2 parts nano-silica and 0.6 parts micron-sized boron nitride, a compound, with the former improving interfacial bonding, synergistically retardant, and constructing a hydrophobic structure, and the latter optimizing thermal conductivity uniformity and high-temperature stability, with moderate dosage to avoid agglomeration and increased costs. All components work synergistically within the same system to achieve a balance of multiple properties including fire resistance, impact resistance, vibration reduction, sound absorption, hydrophobicity, and lightweighting.

[0029] Preferably, the halogen-free high-temperature resistant phenolic resin adhesive is a boron-modified thermosetting phenolic resin with a solid content of 72% ± 2% and a free phenol content ≤ 0.3%. This resin, through boron-oxygen bond crosslinking, significantly improves the system's heat resistance and high-temperature char residue. Furthermore, it is halogen-free and low-smoke, exhibiting high bonding strength and good dimensional stability after curing, ensuring the interfacial bonding force of the fiber network without affecting the material's Class A non-flammability. In addition, this resin is compatible with the temperature range for zoned hot-pressing curing and meets the low-VOC environmental protection requirements for automotive interiors.

[0030] The present invention also provides a method for preparing the above-mentioned fiber composite material, comprising the following steps: Basalt fibers were graded by length and subjected to differential surface modification with silane treatment agent. After drying, hydrophobic basalt fibers, basalt fibers modified with coupling agent containing polar anchoring sites, and inert basalt fibers were obtained. A multi-channel synchronous airflow web-forming device is used to simultaneously lay up and form hydrophobic basalt fibers, basalt fibers modified with a coupling agent containing polar anchoring sites, and basalt fibers treated with inertization in a single operation, thereby preparing a continuous gradient fiber preform. Specifically: the hydrophobic basalt fibers are compacted and web-laid using a first pressure airflow process to form the first region of the continuous gradient fiber preform; the basalt fibers modified with the coupling agent containing polar anchoring sites are laid up using a second pressure airflow process with a three-dimensional random interweaving web to form the second region of the continuous gradient fiber preform; and the inert basalt fibers are loosely web-laid using a third pressure airflow process to form the third region of the continuous gradient fiber preform. The airflow kinetic energy or compaction intensity of the first, second, and third pressure airflow processes decreases sequentially. Along the thickness direction of the continuous gradient fiber preform, the second region is located between the first and third regions. Prepare an impregnation slurry, spray the impregnation slurry onto the surface of the third region of the continuous gradient fiber preform, apply negative pressure to one side of the first region of the continuous gradient fiber preform, and obtain the impregnated continuous gradient fiber preform. The impregnated gradient fiber preform is hot-pressed using an independently temperature-controlled upper and lower mold, and then cooled in a furnace to obtain the fiber composite material.

[0031] This preparation method achieves precise construction of continuous gradient integrated composite materials through fiber graded modification, synchronous airflow web formation, unilateral gradient negative pressure impregnation, and zoned temperature-controlled hot pressing curing. First, graded basalt fibers are differentiated using different silane treatment agents, giving each layer interfacial properties such as hydrophobicity, anchoring, and anti-clogging. Then, a multi-channel synchronous airflow web formation device is used for one-time lamination, directly forming a preform with progressively decreasing airflow energy and compaction strength, resulting in a continuously varying fiber length, arrangement, and density along the thickness. This eliminates the traditional adhesive interface, avoids the risk of interlayer delamination, simplifies the process, and improves continuity. Next, unilateral gradient impregnation using a loose layer spraying and a dense layer negative pressure is employed. The porosity gradient of the preform allows the damping slurry to migrate directionally and precisely accumulate in the middle layer, ensuring damping function while avoiding clogging of the sound-absorbing pores. Finally, through zoned hot pressing with independent temperature control of the upper and lower molds and slow cooling in the furnace, the curing conditions of each layer are matched to ensure interlayer bonding. At the same time, by utilizing the difference in thermal expansion between the fiber and the matrix, micron-level hydrophobic channels are generated in situ at the fiber nodes, achieving self-hydrophobicity and resistance to mud and water without the need for additional coatings. The entire process combines structural integration, performance gradient, functional precision, and mass production adaptability, achieving a comprehensive balance of fire resistance and impact resistance, damping and vibration reduction, sound absorption and noise reduction, weather resistance and stability, and lightweight design.

[0032] In some embodiments, during one-time synchronous lay-up molding, the density of the hydrophobicated basalt fibers laid in the first region is 125~145 kg / m³. 3 ; and / or, the density of the basalt fibers modified with a polar anchoring coupling agent laid in the second region is 80~100 kg / m³. 3 ; and / or, the density of the inertized basalt fibers laid in the third region is 40~60 kg / m³. 3 .

[0033] Preferably, the density of the hydrophobicated basalt fibers laid in the first region is 145 kg / m³. 3 The density of the basalt fibers modified with a polar anchoring coupling agent laid in the second region is 100 kg / m³. 3 The density of the inertized basalt fibers laid in the third area is 60 kg / m³. 3 Zone 1: 145 kg / m³ 3 The high density of the fibers, combined with their oriented arrangement, forms a dense and continuous surface structure after subsequent hot-pressing and curing. This provides structural support for impact resistance and thermal barrier properties. (Second region: 100 kg / m²) 3 The medium density provides ample load-bearing space and physical anchoring points for the damping grout, ensuring vibration reduction, while also acting as a density transition buffer to mitigate the structural differences between the inner and outer layers, avoiding the risk of delamination caused by interlayer stress concentration. (Third region: 60 kg / m³) 3 The low-density, loose structure retains a large number of interconnected pores, which not only supports the high-efficiency sound absorption and lightweight effect of the final product, but also provides a smooth penetration path for the slurry during the one-sided negative pressure impregnation stage. At the same time, the density gradient is precisely matched with the fiber length gradation and the air kinetic energy gradient of the web laying, realizing the natural interweaving and entanglement of interlayer fibers during the synchronous web laying process. This eliminates the clear adhesive interface from the preform stage, laying the foundation for the long-term structural stability of the finished product. It also provides porosity gradient conditions for the directional migration and precise enrichment of the middle layer of the damping slurry, avoiding the blockage of the inner layer sound absorption pores by the slurry, and achieving a synergistic improvement in vibration reduction and sound absorption performance.

[0034] In some embodiments, the viscosity of the impregnation slurry is 800~1200 mPa. The negative pressure applied to one side of the first region of the continuous gradient fiber preform is 0.06~0.09 MPa.

[0035] Preferably, the viscosity of the impregnation slurry is 1000 mPa. The negative pressure applied to one side of the first region of the continuous gradient fiber preform is 0.075 MPa. (1000 mPa) The slurry viscosity of s combines suitable fluidity and wettability. It avoids excessive penetration into the inner porous region due to negative pressure, which could clog sound-absorbing pores and weaken the noise reduction effect if the viscosity is too low, nor would it remain only on the surface of the preform if the viscosity is too high, failing to fully wet the middle fiber network and resulting in insufficient damping and vibration reduction performance. Combined with 0.075... The unilateral negative pressure driving force of MPa allows the slurry to migrate directionally from the loose third region to the dense first region. Relying on the porosity gradient of the preform itself, it naturally accumulates in the middle layer interwoven fiber network. This ensures that the damping component and the modified fiber with polar anchoring sites are fully combined to form a solid in-situ damping layer to stably dissipate vibration energy. At the same time, it only forms a small amount of interface wetting on the outer layer dense fiber, without damaging the dense structure and hydrophobic flow channels of the surface layer. It also avoids the inner layer sound-absorbing pores being filled by the slurry. Ultimately, it achieves a precise layered distribution of damping function, taking into account both vibration reduction and sound absorption acoustic performance. It also ensures that the fireproof and impact-resistant outer layer and the lightweight inner layer structural characteristics are not negatively affected by the impregnation process.

[0036] In some embodiments, the control parameters of the mold with independent temperature control for the upper and lower molds include: the mold temperature corresponding to the first region is controlled at 200~230℃, the mold temperature corresponding to the third region is controlled at 150~180℃, and the average molding pressure is 0.7~0.8 MPa.

[0037] Preferably, the control parameters of the independently temperature-controlled upper and lower molds include: the mold temperature corresponding to the first region is controlled at 215℃, the mold temperature corresponding to the third region is controlled at 165℃, and the average molding pressure is 0.75 MPa. This independently temperature-controlled hot pressing process for the upper and lower molds establishes a continuous temperature gradient along the thickness direction, precisely matching the functional and component curing requirements of each layer. The higher temperature in the first region promotes the full cross-linking of the outer phenolic resin, forming a dense and high-strength structure to ensure the impact resistance and fire resistance of the surface layer; the lower temperature in the third region prevents the inner resin from flowing and clogging the pores, maintaining a loose and porous structure to ensure sound absorption performance and lightweight performance; the transition temperature of the middle layer allows the damping slurry to cure moderately, retaining viscoelasticity and promoting synchronous cross-linking between layers to form a continuous structure without interfaces, eliminating the risk of stress concentration and delamination. In addition, the temperature gradient along the thickness direction, combined with the slow cooling process in the furnace, can utilize the difference in thermal expansion between the fiber and the matrix to generate micron-level hydrophobic channels in situ at the fiber nodes, achieving mud and water resistance without additional coatings. Ultimately, through gradient curing control, a synergistic improvement in protection, vibration reduction, sound absorption, weather resistance, and lightweighting is achieved.

[0038] The present invention also provides a wheel arch liner comprising the aforementioned fiber composite material.

[0039] The present invention also provides a new energy vehicle, including a wheel and a wheel arch liner disposed inside the wheel, the wheel arch liner being made of the aforementioned fiber composite material.

[0040] Example 1: Raw material preparation: By weight, the raw material composition is as follows: 90 parts graded basalt fiber, 9 parts halogen-free high-temperature resistant phenolic resin binder, 11 parts flame-retardant butyl damping slurry, 1.2 parts nano silica, and 0.6 parts micron boron nitride.

[0041] The graded basalt fibers include: basalt fibers with a length of 4 mm that have undergone hydrophobic treatment, basalt fibers with a length of 10 mm that have been modified with a coupling agent containing polar anchoring sites, and basalt fibers with a length of 18 mm that have undergone inert treatment. All of the above basalt fibers have a diameter of 8 μm. The preferred halogen-free high-temperature resistant phenolic resin binder is boron-modified thermosetting phenolic resin. The flame-retardant butyl damping slurry is a water-based functional slurry, comprising: 45 parts butyl rubber latex, 10 parts hydrogenated C5 petroleum resin, 30 parts halogen-free flame-retardant compounding agent, 0.8 parts polyurethane rheology modifier, 0.5 parts silane coupling agent KH-550, 0.3 parts silicone defoamer, and 13.4 parts deionized water. The halogen-free flame-retardant compounding agent is composed of ammonium polyphosphate and magnesium hydroxide mixed in a 2:1 mass ratio. By adjusting the solid content and the amount of rheology modifier added, the slurry viscosity can be stably controlled at 1000 mPa. s.

[0042] Preparation steps: (1) Fiber grading and modification: The three length specifications of basalt fibers obtained by sieving were ultrasonically cleaned with anhydrous ethanol for 10 min to remove surface dust and spinning auxiliary agent residues. After pre-drying at 60℃, they were subjected to differential surface modification with silane hydrolysis solution. All modification solutions were used with anhydrous ethanol and deionized water in a volume ratio of 9:1 as solvents and were pre-stirred and hydrolyzed for 30 min before use.

[0043] Basalt fibers with a length of 4 mm were immersed in a 1% (w / w) dodecyltrimethoxysilane hydrolysate for 15 min to complete mild hydrophobic modification; basalt fibers with a length of 10 mm were immersed in a 1.5% (w / w) γ-aminopropyltriethoxysilane (KH-550) hydrolysate for 20 min to complete highly active anchoring modification; and basalt fibers with a length of 18 mm were immersed in a 0.8% (w / w) methyltriethoxysilane hydrolysate for 12 min to complete inert protective modification. After being drained, the modified fibers were uniformly dried at a constant temperature of 70℃ for 25 min. The graded modified basalt fibers exhibit different properties. Specifically, the hydrophobicated basalt fibers have a pure water contact angle of 90 ± 3 degrees, achieving a slightly hydrophobic level while maintaining both mud-water conductivity and interfacial bonding strength with phenolic resin. The basalt fibers modified with a coupling agent containing polar anchoring sites have a surface amino grafting content ≥ 1.2 μmol / m². 2 The basalt fibers possess sufficient polar anchoring sites, enabling them to form a stable chemical bond with the damping slurry. The inertized basalt fiber surface has a pure water contact angle of 70 ± 5 degrees and a low content of surface-active hydroxyl groups, significantly reducing interfacial adhesion with the damping slurry and effectively minimizing residual adhesion of the slurry in the inner pores, thus preventing blockage of the sound absorption channels. The surface-modified basalt fibers are then sprayed with a halogen-free, high-temperature resistant phenolic resin binder using an aerosol spraying process. After application, the fibers are dried with low-temperature hot air until they are dry and dispersed for later use.

[0044] (2) Synchronous airflow web formation: A synchronous airflow web formation device equipped with a three-channel independent air supply system is adopted. Three sets of web formation heads are arranged sequentially along the direction of the web belt, with a vertical center distance of 120 mm between adjacent web formation heads. The running speed of the forming web belt is set to 2.5 m / min. The three types of graded modified basalt fibers are pre-measured according to the target dry blank density and fed into the corresponding feeding bins. The airflow pressure and settling velocity are controlled by independent air ducts to achieve differentiated web formation: For basalt fibers that have undergone hydrophobic treatment, an air supply pressure of 0.20 MPa and a settling velocity of 13 m / s are used. The high-pressure directional airflow drives the fibers to settle in a transverse orientation. The fiber feeding rate is matched to 4.35 kg / (m 2 (min), to control the dry billet density in this area to be stable at 145 kg / m³ 3 This forms an impact-resistant and fireproof layer. Corresponding to basalt fibers modified with a coupling agent containing polar anchoring points, an air supply pressure of 0.14 MPa and a settling velocity of 9 m / s are used. Turbulent airflow drives the fibers to settle in a three-dimensional, randomly interwoven state, with a fiber feeding rate of 2.5 kg / (m²). 2 To control the density of the dry blank in this area to be stable at 100 kg / m³, a gradient damping vibration reduction layer is formed. Corresponding to the inertized basalt fibers, an air supply pressure of 0.08 MPa and a settling velocity of 6 m / s are used. The low-pressure, slow-sinking airflow supports the fibers to settle in a vertical, three-dimensional, loose state. The fiber feeding rate is matched to 1.5 kg / (m³). 2 (min), control the dry billet density in this area to be stable at 60 kg / m³ 3 This forms a porous, sound-absorbing, lightweight layer; three sets of mesh laying heads start operating simultaneously, and fibers are layered and laid on the continuously running forming mesh belt, with fibers naturally interlacing and entangled between layers, forming a continuous gradient fiber preform without obvious adhesive interfaces in one step.

[0045] (3) Negative pressure gradient impregnation: A single-sided integral suction negative pressure impregnation fixture is adopted. The upper part of the fixture is a normal pressure chamber with an atomizing spray system, the lower part is a sealed negative pressure chamber, and the middle part is separated by a porous support mesh plate. The continuous gradient fiber preform is placed flat with the impact-resistant fireproof layer facing down and the supporting mesh plate facing up, while the porous sound-absorbing lightweight layer faces up. The lower negative pressure cavity is connected to a vacuum system to apply a uniform negative pressure to the outer layer of the preform. The vacuum degree of the lower negative pressure cavity is set to 0.075 MPa as the core impregnation driving force. Based on the structural characteristics of the preform, the density increases and the porosity decreases from the inside to the outside in the thickness direction. The fluid permeation resistance gradually increases along the thickness direction, and the negative pressure naturally attenuates when it is transmitted inward. This results in a gradient distribution with the highest negative pressure in the impact-resistant fireproof layer, the second highest in the gradient damping vibration reduction layer, and the lowest in the porous sound-absorbing lightweight layer. The equivalent negative pressure of the impact-resistant fireproof layer is about 0.075 MPa; the equivalent negative pressure of the gradient damping vibration reduction layer is about 0.050 MPa; and the equivalent negative pressure of the porous sound-absorbing lightweight layer is about 0.020 MPa.

[0046] With a viscosity of 1000 mPa Flame-retardant butyl damping slurry of s is evenly sprayed onto the upper surface of the inner layer of the billet through the upper atomizing nozzle. The total spray volume is precisely controlled at 12% of the total dry billet mass, and the spraying time is 8 seconds. After spraying, negative pressure suction is maintained for 12 seconds. Under negative pressure, the slurry permeates from the inner layer to the outer layer along the thickness direction. During the process, due to the physical interception of the three-dimensional interwoven fibers in the middle layer and the chemical adsorption of the polar anchoring sites, the slurry preferentially accumulates in the gradient damping layer. Due to the high permeability resistance of the dense structure, the impact-resistant fireproof layer only forms a small amount of interfacial wetting. Due to the low adhesion characteristics of the inert fibers, the porous sound-absorbing lightweight layer only retains a small amount of slurry. Ultimately, a gradient impregnation effect is achieved, with the gradient damping layer enriched and the impact-resistant fireproof layer and the porous sound-absorbing layer only slightly wetting. The degree of impregnation is controlled by the linkage of the total spray volume, the negative pressure value, and the suction time. The layer weight gain rate is used as the judgment standard: after impregnation and curing, the quality change is tested by peeling off the layers along the thickness direction. The damping slurry adhesion weight gain rate of the impact-resistant fireproof layer and the porous sound-absorbing layer is ≤2%, which means that the requirement of interfacial slight wetting has been met. After suction is completed, the blank is removed by breaking the vacuum, and the gradient impregnation process is completed.

[0047] (4) Partitioned hot pressing curing: The integrated gradient hot pressing curing process with independent temperature control and thickness limit of the upper and lower molds is adopted; the nominal surface pressure of the cavity is controlled at 0.75 MPa, the outer mold temperature is 215℃, and the inner mold temperature is 165℃; through the heat conduction attenuation along the thickness direction, a stable curing temperature field of about 185℃ is formed in the middle layer; relying on the decreasing compression resistance of the integrated gradient blank from the outside to the inside, and with the mold limit locking the total compression, the outer layer reaches the densification degree corresponding to 0.75 MPa compaction pressure, the inner layer reaches the pore retention and shaping effect corresponding to 0.2 MPa compaction pressure, and the middle layer naturally forms a damping curing environment corresponding to 0.45 MPa compaction pressure; the heating rate is controlled at 2.5℃ / min, and the heat preservation and curing is carried out for 15 min; after the heat preservation is completed, the furnace is slowly cooled and shaped, and the difference in thermal expansion coefficient between basalt fiber and resin binder is used to generate 2~4 μm hydrophobic flow micropore channels in situ at the fiber interlacing nodes.

[0048] Example 2: The preparation steps in this embodiment are the same as in Embodiment 1, except that the density of different regions of the preform formed by adjusting the air supply parameters of each channel and the fiber feeding rate in the synchronous airflow web laying step is different. Specifically: For basalt fibers treated with hydrophobicity, a high-pressure directional airflow of 0.16 MPa and a settling velocity of 11 m / s was used to drive the fibers to settle uniformly in a lateral orientation. The fiber feeding rate was matched to 3.75 kg / (m²). 2 (min), to control the dry billet density in this area to be stable at 125 kg / m³ 3This forms an impact-resistant and fireproof layer. Corresponding to basalt fibers modified with a coupling agent containing polar anchoring points, an air supply pressure of 0.10 MPa and a settling velocity of 7 m / s are used. Turbulent airflow drives the fibers to settle in a three-dimensional, randomly interwoven state. The fiber feeding rate is matched to 2 kg / (m²). 2 (min), control the dry billet density in this area to be stable at 80 kg / m³ 3 This forms a gradient damping layer; corresponding to the inertized basalt fibers, a supply air pressure of 0.06 MPa and a settling air velocity of 4 m / s are used. The low-pressure, slow-settling airflow supports the fibers to settle in a vertical, three-dimensional, loose state. The fiber feeding rate is matched to 1 kg / (m²). 2 (min), control the dry billet density in this area to be stable at 40 kg / m³ 3 This forms a porous, sound-absorbing, lightweight layer.

[0049] Example 3: The preparation steps in this embodiment are the same as in Embodiment 1, except that the density of different regions of the preform formed by adjusting the air supply parameters of each channel and the fiber feeding rate in the synchronous airflow web laying step is different. Specifically: For basalt fibers treated with hydrophobicity, a high-pressure directional airflow of 0.18 MPa and a settling velocity of 12 m / s was used to drive the fibers to settle uniformly in a lateral orientation. The fiber feeding rate was matched to 4.05 kg / (m²). 2 (min), to control the dry billet density in this area to be stable at 135 kg / m³ 3 This forms an impact-resistant and fireproof layer. Corresponding to basalt fibers modified with a coupling agent containing polar anchoring points, an air supply pressure of 0.12 MPa and a settling velocity of 8 m / s are used. Turbulent airflow drives the fibers to settle in a three-dimensional, randomly interwoven state, with a fiber feeding rate of 2.25 kg / (m²). 2 (min), control the dry billet density in this area to be stable at 90 kg / m³ 3 This forms a gradient damping layer; corresponding to the inertized basalt fibers, a supply air pressure of 0.07 MPa and a settling air velocity of 5 m / s are used. The low-pressure, slow-settling airflow supports the fibers to settle in a vertical, three-dimensional, loose state. The fiber feeding rate is matched to 1.25 kg / (m²). 2 (min), control the dry billet density in this area to be stable at 50 kg / m³ 3 This forms a porous, sound-absorbing, lightweight layer.

[0050] Example 4: The preparation steps in this embodiment are the same as in Example 1, except that the formulation of the flame-retardant butyl damping slurry used is adjusted as follows: 45 parts butyl rubber latex, 10 parts hydrogenated C5 petroleum resin, 30 parts halogen-free flame-retardant compounding agent, 1.2 parts polyurethane rheology modifier, 0.5 parts silane coupling agent KH-550, 0.3 parts organosilicon defoamer, and 13.0 parts deionized water. The viscosity of the slurry is adjusted to be stable at 1200 mPa. s.

[0051] Example 5: The preparation steps in this embodiment are the same as in Example 1, except that the formulation of the flame-retardant butyl damping slurry is adjusted as follows: 45 parts butyl rubber latex, 10 parts hydrogenated C5 petroleum resin, 30 parts halogen-free flame-retardant compounding agent, 0.4 parts polyurethane rheology modifier, 0.5 parts silane coupling agent KH-550, 0.3 parts organosilicon defoamer, and 13.8 parts deionized water. The viscosity of the slurry is adjusted to be stable at 800 mPa. s.

[0052] Example 6: The preparation steps in this embodiment are the same as in Embodiment 1, except that the amount of raw materials has been adjusted. Specifically, the following materials are used: 93 parts graded basalt fiber, 11 parts boron-modified thermosetting phenolic resin binder, 14 parts flame-retardant butyl damping slurry, 1.8 parts nano silica, and 0.9 parts micron boron nitride.

[0053] Example 7: The preparation steps in this embodiment are the same as in Example 1, except that the amount of raw materials has been adjusted. Specifically, the following materials are used: 88 parts graded basalt fiber, 7 parts boron-modified thermosetting phenolic resin binder, 9 parts flame-retardant butyl damping slurry, 1 part nano silica, and 0.4 parts micron boron nitride.

[0054] Comparative Example 1: The preparation steps for this comparative example are the same as in Example 1, except that the basalt fibers are not subjected to differentiated grade modification. Basalt fibers of three lengths after sieving are used directly without any silane hydrolysis solution impregnation modification treatment, and are directly fed into the air-laid web process after drying at 60°C.

[0055] Comparative Example 2: The preparation steps of this comparative example are the same as those in Example 1, except that the impact-resistant fireproof layer, the gradient damping vibration reduction layer, and the porous sound-absorbing lightweight layer use basalt fibers of the same length, and all are uniformly surface-modified with γ-aminopropyltriethoxysilane (KH-550). The synchronous airflow web-laying process uses a uniform air supply pressure of 0.12 MPa and a settling velocity of 8 m / s. Under the premise that the fiber feeding rate remains unchanged, the final overall dry bulk density is 90 kg / m³. 3 It produces a uniformly structured preform rather than a fibrous preform with a continuous density gradient.

[0056] Comparative Example 3: The preparation steps of this comparative example are the same as those of Example 1, except that fiber preforms for the impact-resistant fireproof layer, the gradient damping vibration reduction layer, and the porous sound-absorbing lightweight layer are prepared independently. After impregnation and pre-curing of each layer, phenolic resin adhesive is coated between the layers for lamination and bonding, and then the whole is hot-pressed and cured to obtain the finished product. The fiber modification, density, and slurry loading of each layer are consistent with the corresponding layer in Example 1. The raw material formula and monomer parameters of each layer are also the same as those of the corresponding layer in Example 1. The remaining preparation parameters are the same as those in Example 1. The total thickness of the obtained finished product is the same as that in Example 1.

[0057] Comparative Example 4: The preparation steps for this comparative example are the same as in Example 1, except that a uniform, whole-body immersion impregnation is used instead of a single-sided gradient negative pressure impregnation. The total sizing amount is the same as in Example 1, and all other conditions are the same as in Example 1. The continuous gradient fiber preform is completely immersed in a solution with a viscosity of 1000 mPa. The sample was immersed in flame-retardant butyl damping slurry for 15 seconds. After removal, the total slurry load was controlled by roller pressing, the same as in Example 1, to ensure that the damping slurry was evenly distributed in the three-layer structure. The fiber modification, web laying parameters, and hot pressing curing parameters were the same as in Example 1. The remaining preparation steps were the same as in Example 1.

[0058] Comparative Example 5: Channels without micropores The preparation steps for this comparative example are the same as in Example 1, except that a rapid cooling process is used instead of slow furnace cooling, thus preventing the formation of micron-sized hydrophobic flow-guiding micropores. After hot pressing and curing, the mold is rapidly cooled using forced air cooling at a rate of approximately 10°C / min. After cooling to room temperature, the mold is opened and the part is removed. The raw material ratio, fiber modification, web laying parameters, impregnation process, and hot pressing and curing parameters are all the same as in Example 1.

[0059] Performance test results: The fire resistance rating test shall be conducted in accordance with the test principle of UL 2596; the fire resistance limit test at 800℃ shall be conducted in accordance with the test principle of GB8624; the average weighted sound insulation test shall be conducted in accordance with the test principle of ISO 10140-2; the test method for resistance to crushed stone impact shall be conducted in accordance with the test principle of ISO 20567-1; the high and low temperature cycling performance test shall be conducted in accordance with the test principle of GB / T2423.22; the water absorption and density test method shall be conducted in accordance with the test principle of GB / T 5480; and the VOC test method shall be conducted in accordance with the test principle of GB / T 27630-2011.

[0060] The test method for the sound insulation performance retention rate in humid environments is as follows: The sample to be tested was first placed in a standard environment of 23℃ ± 2℃ and 50% ± 5% relative humidity for 24 hours, and the initial weighted sound insulation was tested according to ISO 10140-2 as the baseline value. Then, the sample was placed in a constant humidity and heat test chamber with a temperature of 40℃ ± 2℃ and a relative humidity of 93% ± 3% for 48 hours to ensure that the fiber and bonding system reached sufficient moisture absorption equilibrium. The sample was then removed and allowed to stand for 30 minutes in a standard environment to allow the surface free moisture to evaporate naturally. The weighted sound insulation was then tested immediately using the same method, and the performance retention rate was calculated.

[0061] Table 1 Performance test results of each embodiment and comparative example

[0062] As can be seen from the test data in the table, Example 1 has the best overall performance, with a fire resistance limit of 132 min at 800℃, an average weighted sound insulation of 47.5 dB, a sound insulation performance retention rate of 96% in humid environments, and a water absorption rate of only 0.9%. It also showed no damage or deformation in the tests of impact resistance to gravel and high and low temperature cycling. This indicates that the composite fiber prepared by the process provided by this invention has good comprehensive performance and can effectively solve the problems of existing new energy vehicle wheel arch lining materials that are difficult to achieve A-level fire resistance, wide-frequency vibration reduction, fatigue resistance, mud and water resistance, and lightweight.

[0063] Compared to Example 1, Comparative Example 1 did not undergo differentiated graded modification of basalt fibers. Its water absorption rate increased to 3.6%, the average weighted sound insulation decreased by 9.5 dB, the sound insulation performance retention rate in humid environments was only 82%, the high and low temperature cycling performance retention rate was only 82%, and microcracks appeared at the interface after high and low temperature cycling. This indicates that differentiated graded modification of basalt fibers is the basis for forming a dense gradient structure, blocking water penetration, and ensuring interfacial bonding performance.

[0064] Compared to Example 1, Comparative Example 2 did not grade the basalt fibers and used the same airflow pressure to lay the web, forming a uniform density green body structure. Its fire resistance limit was significantly reduced to 92 min, the lowest among all groups, and its impact resistance was also significantly lower. This shows that the continuous gradient structure is crucial for fire resistance limit and impact resistance.

[0065] Compared to Example 1, Comparative Example 3 employed a traditional process of layered preparation and adhesive bonding. Test results showed that the composite material prepared using this method exhibited significant interlaminar cracking after high and low temperature cycling, and slight interlaminar delamination occurred during impact testing with gravel. Furthermore, its fire resistance at 800℃, average weighted sound insulation, and sound insulation performance retention in humid environments were significantly lower. This indicates that the integrated structure obtained through synchronous airflow web laying has advantages over traditional adhesive-bonded structures in terms of fire resistance, impact resistance, and resistance to high and low temperature cycling.

[0066] Compared to Example 1, Comparative Example 4 did not employ a gradient negative pressure impregnation process. Instead, it used a whole-body immersion method, directly immersing the entire preform in flame-retardant butyl damping slurry. Performance test results showed that the composite material prepared in Comparative Example 4 had significantly lower average weighted sound insulation and sound insulation performance retention rate in humid environments. This indicates that gradient negative pressure plays a crucial role in optimizing sound absorption and insulation performance and protecting acoustic channels.

[0067] Compared to Example 1, Comparative Example 5, which was rapidly cooled after hot pressing and could not form microporous channels, resulted in a composite material with a water absorption rate of 3.3% and a sound insulation performance retention rate of only 83% in humid environments. This indicates that the microporous channel structure constructed by slow cooling in the furnace plays a crucial role in inhibiting moisture intrusion and maintaining performance stability under humid conditions, compared to the dense structure obtained by rapid cooling.

[0068] In summary, the processes of basalt fiber graded modification, synchronous airflow web laying, negative pressure gradient impregnation, and slow cooling pore formation in the furnace are all complementary and indispensable, and synergistically achieve the comprehensive effects of high fire resistance, high sound insulation, low water absorption, and excellent impact resistance and temperature cycling resistance of fiber composite materials.

[0069] In the description of this specification, the references to terms such as "one embodiment / mode," "some embodiments / modes," "example," "specific example," or "some examples," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment / mode or example is included in at least one embodiment / mode or example of the present invention. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment / mode or example. Moreover, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments / modes or examples. Furthermore, without contradiction, those skilled in the art can combine and integrate the different embodiments / modes or examples described in this specification, as well as the features of different embodiments / modes or examples.

[0070] It should be noted that in this invention, relational terms such as "first" and "second" are used merely to distinguish one entity or operation from another, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Furthermore, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such a process, method, article, or apparatus. Without further limitations, an element defined by the phrase "comprising one..." does not exclude the presence of other identical elements in the process, method, article, or apparatus that includes said element. In this invention, "a plurality of" means at least two, such as two, three, etc., unless otherwise expressly specified.

[0071] The above description is merely a specific embodiment of the present invention, enabling those skilled in the art to understand or implement the invention. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the invention. Therefore, the present invention is not to be limited to the embodiments shown herein, but is to be accorded the widest scope consistent with the principles and novel features of the invention herein.

Claims

1. A fiber composite material, characterized in that, The fiber composite material comprises, in sequence, an impact-resistant fireproof layer, a gradient damping vibration reduction layer, and a porous sound-absorbing lightweight layer, wherein: The material of the impact-resistant fireproof layer includes hydrophobically treated basalt fiber and flame-retardant components. The material of the gradient damping vibration reduction layer includes basalt fiber modified with a coupling agent containing polar anchoring points and flame-retardant components; The porous sound-absorbing lightweight layer is made of inertized basalt fibers and flame-retardant components.

2. The fiber composite material according to claim 1, characterized in that, The hydrophobicated basalt fibers are 3-5 mm in length; and / or, The hydrophobically treated basalt fibers have a diameter of 6-12 μm; and / or, The basalt fibers modified with a polar anchoring coupling agent have a length of 8-12 mm; and / or, The basalt fibers modified with a polar anchoring coupling agent have a diameter of 6–12 μm; and / or, The inertized basalt fibers are 15-20 mm in length; and / or, The inertized basalt fibers have a diameter of 6~12 μm.

3. The fiber composite material according to claim 1, characterized in that, The basalt fibers in the impact-resistant fireproof layer, after being treated with hydrophobicity, are arranged in a transverse orientation; and / or The basalt fibers modified with a coupling agent containing polar anchoring points in the gradient damping layer exhibit a three-dimensional, randomly interwoven arrangement; and / or The basalt fibers in the porous sound-absorbing lightweight layer, which have undergone inertization treatment, are arranged vertically in a three-dimensional manner.

4. The fiber composite material according to claim 1, characterized in that, The density of the impact-resistant fireproof layer is ρ1, the density of the gradient damping vibration reduction layer is ρ2, the density of the porous sound-absorbing lightweight layer is ρ3, and so on, decreasing sequentially. ρ1 > ρ2 > ρ3; and / or, ρ1 is 145~180 kg / m 3 ; and / or, ρ2 is 95~125 kg / m 3 ; and / or, ρ3 is 45~70 kg / m 3 .

5. The fiber composite material according to claim 1, characterized in that, The raw materials in the impact-resistant fireproof layer, the gradient damping vibration reduction layer, and the porous sound-absorbing lightweight layer, by weight, include: 88-93 parts of modified basalt fiber, 7-11 parts of halogen-free high-temperature resistant phenolic resin binder, 9-14 parts of halogen-free flame-retardant damping slurry, 1-1.8 parts of nano-silica, and 0.4-0.9 parts of micron boron nitride.

6. A method for preparing the fiber composite material as described in claim 1, characterized in that, Includes the following steps: Basalt fibers were graded by length and subjected to differential surface modification with silane treatment agent. After drying, hydrophobic basalt fibers, basalt fibers modified with coupling agent containing polar anchoring sites, and inert basalt fibers were obtained. A multi-channel synchronous airflow web-forming device is used to simultaneously lay up and form hydrophobic basalt fibers, basalt fibers modified with a coupling agent containing polar anchoring sites, and basalt fibers treated with inertization in a single operation, thereby preparing a continuous gradient fiber preform. Specifically: the hydrophobic basalt fibers are compacted and web-laid using a first pressure airflow process to form the first region of the continuous gradient fiber preform; the basalt fibers modified with the coupling agent containing polar anchoring sites are laid up using a second pressure airflow process with a three-dimensional random interweaving web to form the second region of the continuous gradient fiber preform; and the inert basalt fibers are loosely web-laid using a third pressure airflow process to form the third region of the continuous gradient fiber preform. The airflow kinetic energy or compaction intensity of the first, second, and third pressure airflow processes decreases sequentially. Along the thickness direction of the continuous gradient fiber preform, the second region is located between the first and third regions. Prepare an impregnation slurry, spray the impregnation slurry onto the surface of the third region of the continuous gradient fiber preform, apply negative pressure to one side of the first region of the continuous gradient fiber preform, and obtain the impregnated continuous gradient fiber preform. The impregnated gradient fiber preform is hot-pressed using an independently temperature-controlled upper and lower mold, and then cooled in a furnace to obtain the fiber composite material.

7. The preparation method according to claim 6, characterized in that, In the one-time synchronous layup molding process: The density of the hydrophobicated basalt fibers laid in the first region is 125~145 kg / m³. 3 ; and / or, The density of the basalt fibers modified with a polar anchoring coupling agent laid in the second region is 80~100 kg / m³. 3 ; and / or, The density of the inertized basalt fibers in the third region is 40~60 kg / m³. 3 .

8. The preparation method according to claim 6, characterized in that, The viscosity of the impregnation slurry is 800~1200 mPa. The negative pressure applied to one side of the first region of the continuous gradient fiber preform is 0.06~0.09 MPa; the control parameters of the independently temperature-controlled upper and lower molds include: the mold temperature corresponding to the first region is controlled at 200~230℃, the mold temperature corresponding to the third region is controlled at 150~180℃, and the average molding pressure is 0.7~0.8 MPa.

9. A wheel arch liner, characterized in that, The wheel arch liner comprises the fiber composite material as described in any one of claims 1 to 5.

10. A new energy vehicle, characterized in that, Includes a wheel and a wheel arch liner as described in claim 9 disposed inside the wheel.